Spatial trade-offs and synergies among ecosystem services within a global biodiversity hotspot. (January 2018) - Lin, Shiwei; Wu, Ruidong; Yang, Feiling; Wang, Junjun; Wu, Wei
Highlights: We revealed the spatial interactions among 8 ecosystem services in a mountainous area. High to moderate levels of interactions occured among most pairs of services. Four types of ecosystem service bundles were indentified based on the 8 services. The service distributions correspond well to the regional socio-ecological gradients. Abstract: Managing multiple ecosystem services (ESs) in a win-win manner is a necessary and challenging task. However, our understanding of the spatial interactions among ESs is relatively limited, particularly in mountainous areas. Using the global biodiversity hotspot known as the Three Parallel Rivers Region in Southwest China as a case study, this paper systematically investigated the spatial trade-offs and synergies among 8 ESs (i.e. crop production, livestock-raising, water supply, carbon storage, carbon sequestration, soil retention, habitat support and nature recreation). We mapped the township-level distributions of the 8 ESs and measured their relationships using Spearman's rank correlation coefficients and overlap analyses of ES hotspots/coldspots. Four types of ES bundles were identified by applying the K-means clustering analysis to the 8 ESs. Our results revealed high to moderate levels of interactions among most pairs of ESs. Most provisioning services showed trade-offs with ESs of the other categories, whereas most regulating services demonstrated synergies with other ESs. The ES bundles presented a reasonable set of ecological zones that were characterized by the provisions of different ESs. The spatial patterns of ESs and their interactions corresponded well to the regional socio-ecological gradients in topography, climate and human activities. Our results should have important applications in regional decision-makings on economic development and environmental conservation. This study also provides a good case for demonstrating the complex relationships among ESs in a typical mountainous biodiversity hotspot.